Peran islamic corporate social responsibility dalam memediasi pengaruh ukuran perusahaan, leverage, likuiditas, dan kecukupan modal terhadap kinerja keuangan - Pratiwi, Efa Mega; Yudiana, Fetria Eka (Nur Science Institute, 2023)
This research aimed to determine the effect of company size, leverage, liquidity, and capital adequacy on financial performance as intervening variables in Islamic commercial banks for 2015-2019. The data used is quantitative data, which is measured on a numerical scale. The data type used is secondary data obtained from financial reports of Islamic commercial banks in Indonesia from 2015 to 2019. The method for testing hypotheses uses a path analysis approach. This research shows that the DER, CAR, and ICSR variables significantly affect ROA, but the SIZE and FDR variables have no effect on ROA. The SIZE, DER, and FDR variables significantly affect ICSR, but the CAR variable has no effect on ICSR. The ICSR variable can mediate only the DER variable, while the SIZE, FDR, and CAR variables do not.